Effect of Chronic Khat Chewing on Intima-Media Thickness of Common Carotid Arteries in Yemeni volunteers - Ameen M. Amer; Elsafi A. Abdalla; Amna A. M. Mokhtar (University of Science and Technology, Sana'a, 2021)
Objective: To assess the changes occurring in both common carotid arteries (CCAs) intima-media thickness (IMT) in Yemeni chronic khat chewers using B-mode ultrasonography. Methods: This cross-sectional study was conducted among 195 participants (103 regular khat chewers and 92 non-khat chewers) conveniently selected at the Radiology Department of the University of Science and Technology Hospital (USTH) in Sanaa from August 2017 to August 2018. Data about gender, age, BMI, chewing khat and the period of chewing were collected from participants using a structured questionnaire. B-mode ultrasonography of bilateral CCAs was then performed to measure the IMT. Data were analyzed using suitable statistical tests, and P-values <0.05 were considered statistically significant. Results: The majority of participants with CCA-IMT were males (91.8%) and aged 27 years or younger (59.0%), with a mean age of 27.9 6.8 years. Khat chewers constituted more than half of patients with CCA-IMT. There was no statistically significant difference in the mean values of RT CCA-IMT and LT CCA-IMT between khat chewers and non-khat chewers. The CCA-MIT was significantly higher among male khat chewers compared to male non-chewers (P = 0.004). However, there was no statistically significant difference between khat chewers and non-chewers with respect to the age of 20 years or older (P = 0.301) and BMI of 18.5 kg/m2 or higher (P = 0.888). Age showed a significant positive correlation with RT CCA-IMT (r = 0.380; P < 0.001) and LT CCA-IMT (r = 0.458; P < 0.001) in Khat chewers. In contrast, age showed a significant positive correlation with LT CCA-IMT only in non-khat chewers (r = 0.236; P = 0.024). On the other hand, BMI showed a significant positive correlation with LT CCA-IMT (r = 0.254; P = 0.010) among khat chewers, but no significant correlation was found in CCA-IMT of both sides among non-khat chewers. Among khat chewers, there was a significant positive correlation with RT CCA-IMT (r = 0.273; P = 0.005) and LT CCA-IMT(r = 0.194; P = 0.049). Conclusion: Khat chewing does not lead to a significant difference in CCA-IMT among Yemeni chewers compared to non-chewers. However, the period of chewing may slightly affect the CCA-IMT among khat chewers. Age has a significant positive correlation with CCA-IMT in khat chewers and LT CCA-MIT in non-khat chewers, which could help to determine the contribution of different predisposing factors to atherosclerosis. A significant positive correlation can be found between BMI and LT CCA-MIT among khat chewers.